Distant Metastasis in Pediatric and Adolescent Differentiated Thyroid Cancer: Clinical Outcomes and Risk Factor Analyses - Sugino, Kiminori; Nagahama, Mitsuji; Kitagawa, Wataru; Ohkuwa, Keiko; Uruno, Takashi; Matsuzu, Kenichi; Suzuki, Akifumi; Tomoda, Chisato; Hames, Kiyomi Yamada; Akaishi, Junko; Masaki, Chie; Ito, Koichi (The journal of clinical endocrinology and metabolism, 2020)
Abstract Context The specific characteristics of pediatric and adolescent differentiated thyroid cancer (DTC) is the more frequent occurrence of distant metastasis (DM) compared with adult DTC. Objective To investigate the clinical outcomes of DM in this population and analyze risk factors related to DM. Design, Setting, and Participants Medical records of 171 patients with DTC < 19 years old, who underwent initial surgery between 1979 and 2014 were retrospectively reviewed. Main Outcome Measure Clinical responses to radioiodine (RAI) therapy evaluated by the American Thyroid Association (ATA) guidelines for adult DTC and Response Evaluation Criteria in Solid Tumors (RECIST) criteria. Risk factors related to distant-metastasis-free survival (DMFS). Results DM was observed in 29 patients, and all were lung metastases. The pattern of lung metastasis was classified into 3 categories: macronodular, micronodular, and no apparent nodule (detected only by RAI scintigraphy). Patients with excellent responses according to the ATA guideline criteria or complete remission of the RECIST criteria were most frequently observed in those with no apparent nodule. Significant factors related to DMFS were sex, clinical lymph node metastasis (LNM), extrathyroidal extension, and number of LNM. Subjects were divided into 3 groups according to the number of risk factors: low risk (no risk factors); intermediate risk (1 risk factor); and high risk (≥2 risk factors). Twenty-year DMFS rates in the low-, intermediate-, and high-risk groups were 99.0%, 71.7%, and 28.6%, respectively. Conclusion To achieve the full efficacy of RAI therapy, early diagnosis of DM before apparent metastases appear is desirable. The selective approach would be preferable for pediatric and adolescent DTC.